ANALISIS KINERJA KEUANGAN DAN UKURAN PERUSAHAAN DAN KAITANNYA DENGAN LUAS PENGUNGKAPAN LAPORAN BERKELANJUTAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN INDONESIA PERIODE 2006-2011 - Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
The CSR’s (Corporate Social Responsibility) reported by companies in Indonesia have been regulated in the Act. Company's line of business related to natural resources shall submit the implementation of social and environmental responsibility. This study focused on the mining sector and aims to determine the mining company (listed on the Stock Exchange) that have and have not been compiled SR, the connection of financial performance on the disclosure of SR on mining companies listed on the Stock Exchange, and the connection of firm size on SR disclosures on mining companies listed on the Stock Exchange. There are 23 companies that have not been compiled SR. The results of this study found no connection of financial performance on an ongoing sustainability reporting, but there is the influence of firm size on sustainability reporting.Keyword : sustainability report, financial performance, firm size